Dr. Banda in the making of Malawi - Virmani, K. K. (Delhi : Kalinga Publications, 1992)
History of Malawi during the tenure of H. Kamuzu (Hastings Kamuzu) B anda, b. 1905, first Prime Minister.
Includes bibliographical references (p. [225]-227) and index.
Keywords: Banda, H. Kamuzu -- d. 1997.; Malawi -- History